A new type of microwave dielectric ceramic based on K2O–SrO–P2O5 composition with high quality factor and low sintering temperature. Issue 1 (1st January 2022) - Bao, Jian; Du, Jialun; Liu, Lintao; Wu, Haitao; Zhou, Yuanyuan; Yue, Zhenxing
Abstract: A new type of microwave dielectric ceramics with low dielectric loss was fabricated through a traditional solid-phase method. X-ray diffraction and density tests showed that KSrPO4 ceramics with a single orthorhombic phase could be synthesized and densified at 950 °C, and the crystal structure of KSrPO4 was further confirmed by Rietveld refinement analysis. The densification temperature of KSrPO4 was lower than 961 °C, indicating the ceramics could be used in LTCC devices. Additionally, based on the complex chemical bond theory, some internal parameters of KSrPO4 ceramics were calculated and the effects of these parameters on the properties of KSrPO4 were systematically analyzed for the first time. Furthermore, the composite dielectric constant and loss of KSrPO4 ceramics were analyzed by infrared reflectance spectroscopy, and the theoretical loss and the actual loss were compared. Finally, a vector network analyzer was employed to measure the microwave dielectric properties of all samples. The results showed that KSrPO4 sintered at 950 °C obtain the best microwave dielectric properties, including ε r  = 7.85, Q·f  = 34, 527 GHz (at 10.43 GHz) and τ f  = −14.82 ppm/°C.